PENGEMBANGAN BUKU SAKU CERITA RAKYAT SUB SUKU DAYAK DESA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN DI SEKOLAH DASAR - Warkintin, Warkintin; Kurniati, Agusta; Riberu, Evensius Dimas Hendro; Oktaviani, Ursula Dwi; Putri, Lisia Adelia (STKIP Persada Khatulistiwa Sintang, 2025)
In line with the vision and mission of cultural preservation of the Ministry of National Education and Culture, cultural development is prioritized on Increasing Awareness and Understanding of National Identity and Character; Increasing Public Appreciation of Diversity, as well as Creativity of Cultural Values, traditions, beliefs, history, Art, and Film; Improving the Quality of Management, Protection, Development, and Utilization of Cultural Heritage; Increasing Internalization and Cultural Diplomacy; Development of Cultural Resources; Improving Cultural Facilities and Infrastructure. In fact, in the current global era, the transformation is progressing very rapidly which then leads Indonesian society to a knowledge-based society without losing the national identity. Seeing the current phenomenon in the implementation of the independent curriculum in schools, especially at the elementary school level. Where literacy skills are one of the priorities of educational implementation in schools. However, a constraint is the lack of student interest in reading. One of the causes of student low interest in reading is due to the lack of interesting reading materials for students. This is one of the reasons for the urgency of developing this Pocket Book. The Pocket Book that will be developed with special characteristics based on local culture, namely folklore of the Suku Dayak Desa in Sintang Regency. The method in this research is the Development Method, namely creating and developing a Pocket Book of Folk Stories of the Suku Dayak Desa.